STRESS LEVELS AND INCIDENCE OF HYPERTENSION IN PRODUCTIVE AGE DURING COVID-19 PANDEMIC IN BANJARNEGARA 2 PUBLIC HEALTH CENTRE - Arifah, Istiqlal Nur; -, Sulistyawati (Indonesian Journal for Health Sciences, 2024)
Hypertension is a world public health problem with a high prevalence of cases, especially in productive age. During the COVID-19 pandemic, there was an increase in comorbid cases, including hypertension, due to a lack of physical activity and psychological illnesses. One of the risk factors for hypertension is stress. This study aimed to determine the relationship between stress and the incidence of hypertension in the Banjarnegara 2 Health Center during the pandemic. This study used a cross-sectional design. As many as 65 participants were involved in this study that were selected using purposive sampling. A set of pre-tested questionnaires was adopted from DASS-42 to collect information from the respondents. Analysis was done using the Spearman rank correlation test. Most productive-age respondents during the pandemic at Puskesmas Banjarnegara 2 had moderate stress levels (41.5%), followed by normal high hypertension (38.5%). Spearman rank correlation test showed a significant relationship between stress levels and the incidence of hypertension in productive age during the pandemic in the region   Puskesmas Banjarnegara 2 with a p-value of   0.000 (p0.05). This result showed a positive and robust correlation of 0.743, meaning that stress levels were associated with the incidence of hypertension in productive age during the pandemic.